(untitled) (Anclajes, 2021)
Throughout the 70s, exiled artists of the New Chilean Song –in primis, the band Inti-Illimani– promoted a mass audience of Latin American folk music genres. In the discourse that accompanied Chilean success in the Italian media of the time, we find little insistence on explicit exoticism. Instead, in the newly imported musical genres, there is a certain desire to acknowledge a project of renewal regarding social song, shared by the Italian leftist culture of that time. The New Chilean Song seemed to be an advanced and exemplary realization of that project. By examining a wide range of documents from that time, we understand how the success attributed to Chilean / Andean music in Italy is linked not only to well-known political factors or to the fascination for that novel sound, but also to the ability of some artists to generate interactions in the reception context opened as a result of exile.